PROJECT MANAGEMENT BASED ON AGILE METHODOLOGY (Development Service Industry Management, 2024)
The article considers the Agile methodology as a modern approach to project management, which is based on the principles of adaptive planning, iterative execution, rapid adaptation to changes and continuous improvement. Agile is widely used in dynamic industries, such as IT, but also finds its place in other areas due to its flexibility, efficient use of resources and minimization of risks. The Agile methodology is based on the Agile Software Development Manifesto, which emphasizes the importance of interaction between people, creating products that meet customer needs and process flexibility. The article presents key economic aspects of the methodology, such as maximizing customer value, optimizing resource use, reducing risks and reducing management costs. The use of Agile allows you to respond quickly to changes, minimize errors through short iterations (sprints), and ensure high team productivity through cross-functional collaboration. The article compares Agile with the traditional Waterfall methodology, which is characterized by sequential task execution, careful planning, and a structured approach. Agile offers a flexible, incremental approach with constant collaboration with customers, while Waterfall focuses on fulfilling fixed requirements with an emphasis on documentation and minimizing risks through detailed planning. Tables are provided that demonstrate the key economic aspects of Agile and the characteristics of both methodologies. The results of the study showed that Agile is an effective project management tool in a dynamic market, as it provides a quick response to changes, optimal use of resources, and the creation of products that meet customer needs. In particular, the advantages of Agile are the rapid delivery of results, minimizing costs, and increasing process flexibility. The conclusions state that the choice between Agile and Waterfall depends on the specifics of the project: Agile is suitable for projects with high dynamics of change, while Waterfall is appropriate for stable and predictable projects.
Keywords: project management; Agile; Waterfall; Agile manifesto; adaptation